Effect of silicon and aluminium in ferrite on tensile and impact properties. Issue 15 (13th October 2017) - Pang, J. C.; Xu, B. Y.; Wang, G. D.; Lu, Q.; Wang, J. F.; Yi, H. L.
ABSTRACT: Two ferritic interstitial-free steels with approximately the same amount of solid solution strengthening by addition of 2 wt-% silicon and 4 wt-% aluminium are investigated using quasi-static tensile and dynamic impact tests. The addition of 2 wt-% silicon (2Si) results in brittle fracture in V-notched Charpy impact tests at ambient temperature, whilst the 4 wt-% aluminium-containing (4Al) steel has high absorbed energy of 320 ± 12 J cm −2 . In addition, the 4Al steel has a ductile-to-brittle-transition temperature (DBTT) ∼60°C lower than the 2Si steel. It is proposed that the addition of silicon suppresses dislocation cross-slip at high strain rate and is responsible for the observed cleavage fracture and high DBTT in the 2Si steel. The ease of dislocation slip in the 4Al steel increases the impact toughness.